USE OF PEDAGOGICAL TECHNOLOGIES AND METHODS IN TEACHING THE SCIENCE OF ARCHEOLOGY - Mirsoatova Sayyora Turgunovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article talks about the use of new pedagogical technologies in archeology lectures and seminars. Using the example of the Stone Age, the advantages of using technical tools in teaching students about archaeological sites in Uzbekistan and Central Asia are analyzed.